Invisibility as a structural determinant: Mortality outcomes of Asians and Pacific Islanders experiencing homelessness - Chang, Jamie Suki; Saxton, Katherine; Bright, Georgia; Ryan, Maya S.; Lai, E. Francis; Jorden, Michelle A.; Gutierrez, Andy (Frontiers in Public Health, 2023)
Introduction: Asian and Pacific Islanders (APIs) who are homeless are situated in a social intersection that has rendered them unrecognized, and therefore vulnerable. There has been increasing attention to racial disparities in homelessness, but research into API homelessness is exceedingly rare. The purpose of this study is to examine the causes of death among APIs who died while homeless in Santa Clara County (SCC), and compare these causes to other racial groups. Materials and methods: We report on data obtained from the SCC Medical Examiner-Coroner's Office on unhoused people’s deaths that occurred between 2011-2021 (n=1394), including data on deaths of unhoused APIs (n=87). Results: APIs comprised 6.2% of total deaths of unhoused people. APIs died less often of causes related to drug/alcohol use than all other racial groups (24.1%, compared to 39.3%), and there was a trend towards more API deaths from injuries or illnesses. When APIs were disaggregated into sub-groups (East Asian, South Asian, Pacific Islander), there were notable mortality differences in cause of death, age, and sex. Discussion: We argue that invisibility is a structural determinant of health that homeless APIs face. Though relatively small in numbers, APIs may experience increased vulnerability to specific mortality risks and outcomes due to this structural determinant. To understand the health outcomes of unhoused APIs, it is essential that researchers and policymakers gather and report disaggregated races and ethnicities.